2023
DOI: 10.1088/2053-1591/acb252
|View full text |Cite
|
Sign up to set email alerts
|

Interface strength investigations of 304 stainless steel/T2 red copper T-type brazed joint based on cohesive zone model

Abstract: Gas wave refrigerators are a type of refrigeration equipment with broad application prospects. The oscillating tube, its core component, was manufactured by brazing to improve production efficiency. To study the brazing interface strength, a small 304 stainless steel/T2 red copper T-type brazed joint specimen was designed. The tensile process of the brazed joint was simulated using ABAQUS software based on the bilinear cohesive zone model (CZM), and the results were compared with the experimental tensile resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…M. Salmaliyan [11] carried out shear strength and microhardness tests to investigate the mechanical properties of the joints and found that the presence of eutectic and dendritic solidification increased through Ti addition. Wu et al [12] designed a small 304 stainless steel/T2 red copper T-type brazed-joint specimen to study the brazing interface strength. The results showed that with an increase in cyclic displacement, the crack initiation life decreased, and the crack growth rate increased; Kawashima et al [13] proposed a novel specimen by taking a section of the overall plate-fin heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…M. Salmaliyan [11] carried out shear strength and microhardness tests to investigate the mechanical properties of the joints and found that the presence of eutectic and dendritic solidification increased through Ti addition. Wu et al [12] designed a small 304 stainless steel/T2 red copper T-type brazed-joint specimen to study the brazing interface strength. The results showed that with an increase in cyclic displacement, the crack initiation life decreased, and the crack growth rate increased; Kawashima et al [13] proposed a novel specimen by taking a section of the overall plate-fin heat exchanger.…”
Section: Introductionmentioning
confidence: 99%